Voices and Choices: Critical Information/Media Literacy and Behrman's Practices. Issue 2 (2nd April 2020) - Zanin-Yost, Alessia; Freie, Carrie
ABSTRACT: Studies on information and media literacy focus on describing activities and frameworks individually, and most of the time, connect within the field of library science. However, other frameworks and practices can be used. This case study presents the application of Behrman's Critical Literacy Practices to information and media literacy to engage students to think critically about information within their field of study. The purpose of this research is to model the information behavior of education students through the perspective of constructivist learning. The study used a qualitative method with six upper-level undergraduate education majors. Activities that comprise practices and theories in both education and library sciences are presented to form a continuous exposure to critical thinking. Factors that influenced how students perceived the validity of information came from personal, educational, and societal factors. This research contributes to the ongoing discussion about critical thinking skills in undergraduate students, presenting a model that describes how practices from other fields can be used and incorporated with information and media literacy.